Balanced science 1 - Johns, Geoff; Jones, Mary.; Marchington, Phillip (New York : Cambridge University Press, 1990)
Balanced Science is a two-volume resource designed for use in Key Stage 4 GCSE coordinated science courses. The second editions have been fully updated to match the latest double-award GCSE science syllabuses. Core and extension sections ensure they will be suitable for students from a range of abilities.
Includes index.
Keywords: Science; Science -- Problems, exercises, etc